Síntese verde e parcialmente verde de nanopartículas de prata estabilizadas por galactomanana da fava danta - Pires, Natália da Rocha (2013)
Silver nanoparticles is a topic prominent among nanostructured materials for exhibit optical and electromagnetic properties different from those observed in the bulk metal, but its bactericidal activity, one of their most investigated property. Green synthesis and stabilization of silver nanoparticles green (NPAG) aims to reduce or substitution of reagents used in conventional processes thereby minimizing the harmful effect to the environment. The use of polysaccharides is an green alternative as a reducing and stabilizing agent. The purpose of this study was to synthesize silver nanoparticles using galactomannan of fava danta (Dimorphandra gardneriana) (GFD) as stabilizer and reducing agent. Therefore, syntheses were carried out by two different methods: 1) Galactomannan as a stabilizer and sodium borohydride (NaBH4) as a reducing agent, 2) Green Synthesis: galactomannan acting as a reducing agent and stabilizer, using increased temperature and pH variation as auxiliary resources. Syntheses were perfomed with fixed molar ratio of 1:1 NaBH4/AgNO3. The molar ratio of monosaccharide units of GFD /Ag+ (GFD ratio Ag) varying from 1:1 to 100:1. For green synthesis GFD:Ag 10:1 ration was chosen, the pH was adjusted to 3, 7, 10 and 12, and the systems kept at constant temperature of 50, 70 and 90 °C, with 30 min and 3 h of reaction. All colloid synthesized were analyzed by absorption spectroscopy in the UV-Vis confirming the formation of the band NPAG the appearance of surface plasmon resonance (SPR) in the region of 400 nm. The stability of colloids was also monitored by UV-Vis and even these were stable even after a year of synthesis. For green synthesis, only the solutions in pH 12 at 70 and 90 ° C (FDAg12/70 and FDAg12/90) SPR showed bands in the spectrum of UV-Vis with 30 min of reaction, with similar intensities to those given for colloid obtained with NaBH4 (FDAgBH). FDAgBH, FDAg12/70 and FDAg12/90 colloids showed a negative and low zeta potential, indicating that stability is due to the steric hindrance from polysaccharide chains. The colloids were stable even after drying and redispersion in water. Infrared spectra indicate that the stabilization of NPAg occurs mainly by the hydroxyl groups from GFD. The conductivity of the sample increase with the presence of silver nanoparticles decreasing the thermal stability of the GFD. The galactomannan of fava danta acts as a good stabilizing agent for NPAg colloids synthesized with NaBH4 and a good reducing and stabilizing agent for green synthesis. The colloids obtained from this polysaccharides showed bactericidal effect against gram positive Staphylococcus aureus with increasing of the initial concentration of silver ions.